Diversifikasi Portofolio Kredit, Risiko dan Return Bank - Rahmat Setiawan; Octavia Reniar Putri; Aulia Claraning Sukmawati (Jurnal Akuntansi, 2023)
Banks as financial intermediaries, can diversify their credit portfolios into different sectors. This study aims to determine the effect of credit portfolio diversification on risks borne and returns earned by banks. The sample in this study was 61 conventional commercial banks in Indonesia for the 2012-2014 period with a total of 112 observations. The results show that credit portfolio diversification has a significant negative effect on bank risk and return. In other words, a more diversified credit portfolio can reduce bank risk and return. Keywords: diversification, loan portfolio, bank’s risk, bank’s return